Coupled model for crack-moisture interaction in brittle porous materials. (1st August 2021) - Görtz, J.; Wieprecht, S.; Terheiden, K.
Abstract: Cracks have a major influence on the service life of brittle porous materials like concrete. Especially, the hydraulic properties within the cracked area are significantly changed compared to the uncracked material. Former research often focused exclusively on the prediction of the initiation and growth of cracks or on the moisture transport, while the coupling between the moisture transport and the structural deterioration is rather an emerging topic. Usually, the pore pressure in the crack is treated either acting within the whole cracked element or only at the element interface, while simultaneously the heterogeneity of the crack is neglected. To improve the hydraulic modelling of the crack, a novel coupling approach is investigated in this work. The description is based on a multi-continuum moisture transport model, which is combined with a classical continuum mechanics solver using a smeared tensile crack mechanism. The model incorporates the changes in the pore and crack structure during crack development and is able to consider capillary and surface forces within the crack. The results of this model are in good agreement with measured saturation profiles during moisture ingress into cracked concrete from literature. Furthermore, the modelling of the Koyna dam demonstrates the applicability on large structures and is expected to improve the numerical description of aging processes.